Werk ist Weltform: Rainald Goetz' Buchkomplex »Heute Morgen« - Hintze, Lena (transcript, 2020)
An overall interpretation of Rainald Goetz's book complex »Heute Morgen« which approaches the interior of the texts via their paratext.